Evaluation of tendency towards academic dishonesty levels of psychological counseling and guidance undergraduate students - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
This aim of this study is to investigate tendency towards academic dishonesty levels of undergraduate students. The sample consisted of 303 undergraduate students attending to psychological counseling and guidance department. In this study, Tendency towards Academic Dishonesty Scale was used as data collection tools. Results indicated that no significant differences were found in tendency towards academic dishonesty levels of students in terms of gender, class level, and father education level. On the other hand, significant differences were found in tendency towards academic dishonesty levels of students in terms of mother education level and perceived academic level. Scheffe test was carried out in order to determine among which groups significant differences existed. According to Scheffe test results, academic dishonesty levels of students whose mother education level is graduate was found to be higher than the academic dishonesty levels of students whose mother education levels were illiterate, literate and high school. However, no significant difference was found according to Scheffe test results in perceived academic achievement.
Keywords: Psychological Counseling and Guidance Department; Academic Dishonesty